Perancangan Sistem Informasi Kinerja Pegawai Di PT GETS Berbasis Website Dengan Menggunakan Metode Extreme Programming - Erik Parulian Simamora; Samsoni (CV. Multi Kreasi Media, 2023)
The employee performance information system is a system designed for information purposes regarding the duties of employees at PT GETS. PT GETS is one of the companies engaged in IT services and solutions that does not yet have an employee performance information system. As a result, employees experience difficulties in reporting tasks and reviewing tasks after having to wait for confirmation from their superiors or leaders at the office. In addition, it is difficult for leaders to monitor the results of work reports every time. Therefore, an employee performance information system was designed using the extreme programming method. This employee performance information system is designed to make it easier for leaders to control employee performance, for employees are easier to report work, and easier to receive information about assigned tasks. So that the admin is easier recap the job report data. So it is hoped that the final design of this employee performance information system can be used more efficiently and effectively in management tasks, and job reports at PT GETS.